2022
DOI: 10.1128/jvi.00775-22
|View full text |Cite
|
Sign up to set email alerts
|

A Bispecific Antibody Targeting RBD and S2 Potently Neutralizes SARS-CoV-2 Omicron and Other Variants of Concern

Abstract: The new, highly contagious SARS-CoV-2 Omicron variant caused substantial breakthrough infections and has become the dominant strain in countries across the world. Omicron variants usually bear high mutations in the spike protein and exhibit considerable escape of most potent neutralization monoclonal antibodies and reduced efficacy of current COVID-19 vaccines.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Consistent with this, intranasal vaccines were shown to induce a superior mucosal immunity in animal models, leading to higher protecting immunity against SARS-CoV-2 [ 30 , 31 , 32 ]. Moreover, broadly neutralizing IgA antibodies in mucosal tissues were reported to neutralize SARS-CoV-2 variants including Omicron [ 24 , 33 , 34 ]. Last, antibody-dependent enhancement (ADE), a phenomenon capable of facilitating virus entry and pathogenesis, has mainly observed with IgG rather than IgA through the FcγR involvement [ 35 ]; thus, a potent mucosal IgA response would be mainly protective.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, intranasal vaccines were shown to induce a superior mucosal immunity in animal models, leading to higher protecting immunity against SARS-CoV-2 [ 30 , 31 , 32 ]. Moreover, broadly neutralizing IgA antibodies in mucosal tissues were reported to neutralize SARS-CoV-2 variants including Omicron [ 24 , 33 , 34 ]. Last, antibody-dependent enhancement (ADE), a phenomenon capable of facilitating virus entry and pathogenesis, has mainly observed with IgG rather than IgA through the FcγR involvement [ 35 ]; thus, a potent mucosal IgA response would be mainly protective.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to investigate different antibody formats, bispecific or multispecific, that can simultaneously and synergistically bind to multiple epitopes. [42][43][44][66][67][68][69][70][71][72][73] A study on bispecific antibodies combining anti-RBD and anti-S2 antibodies has been reported. 44 The structure of these bispecific antibodies involved a combination of scFvs from neutralizing antibodies against RBD and S2, arranged in tandem in the scFv-scFv-Fc format.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][66][67][68][69][70][71][72][73] A study on bispecific antibodies combining anti-RBD and anti-S2 antibodies has been reported. 44 The structure of these bispecific antibodies involved a combination of scFvs from neutralizing antibodies against RBD and S2, arranged in tandem in the scFv-scFv-Fc format. Unfortunately, the specific epitope targeted by the anti-S2 antibodies has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of a universal antibody is desired. Such antibodies have already been developed (4,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) , (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), but it is not known whether they have su cient neutralizing activity against the continuously emerging variants of omicron strains(4, 41-54) , (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%